DIGITAL MEDIA, GLOBAL CULTURE, AND GENERATION Z ONLINE SHOPPING BEHAVIOR IN DENPASAR: THE MEDIATING ROLE OF MEDIA USAGE MOTIVATION - I Nyoman Sedana (TOPLAMA, 2026)
This study aims to analyze the influence of digital media exposure and global cultural representation on media usage motivation and online shopping behavior among Generation Z in Denpasar City, while also assessing the mediating role of media usage motivation. A quantitative approach was employed using a cross-sectional survey design with 170 Generation Z respondents (aged 18–29 years) who are active users of social media and e-commerce platforms. Data analysis was conducted using Structural Equation Modeling (SEM) and the Sobel test. The findings reveal that digital media exposure significantly influences media usage motivation (β = 0.322; CR = 2.728; p = 0.006) and online shopping behavior (β = 0.211; CR = 2.501; p = 0.007). Global cultural representation demonstrates a stronger impact on both media usage motivation (β = 0.664; CR = 5.602; p < 0.001) and online shopping behavior (β = 0.603; CR = 5.581; p < 0.001). Furthermore, media usage motivation positively affects online shopping behavior (β = 0.368; CR = 3.899; p < 0.001). The Sobel test results indicate t = 2.273 (digital media) and t = 3.089 (global culture), both exceeding 1.96, thereby confirming that media usage motivation serves as a significant mediator. This study reaffirms the relevance of the Uses and Gratifications (U&G) theory in explaining the digital consumption patterns of Generation Z. The novelty lies in integrating the global culture variable into the U&G framework to explain Generation Z’s online shopping behavior within a culturally rooted urban context (Denpasar), which remains underexplored in the international literature. These findings enrich the discourse on cross-cultural digital consumer behavior and offer practical contributions to digital marketing strategies, digital literacy policies, and the empowerment of MSMEs through e-commerce.